Sperm with fibrous sheath dysplasia and anomalies in head–neck junction: focus on centriole and centrin 1. (5th September 2016) - Moretti, E.; Pascarelli, N. A.; Belmonte, G.; Renieri, T.; Collodel, G.
Summary: Spermatozoa with a rare combination of two monomorphic sperm defects, dysplasia of the fibrous sheath (DFS) and alterations in head–mid‐piece junction were analysed. The main focus was to explore the status of the centriole, a key organisation during fertilisation, using the centrin 1, a calcium‐binding protein linked to this structure. The sperm quality was examined by light, scanning and transmission electron microscopy (SEM, TEM); immunocytochemistry was performed for tubulin, A‐kinase anchor protein 4 (AKAP4) and centrin 1. Spermatozoa showed DFS defect associated with anomalies in head–tail attachment detected by SEM and TEM. Immunolocalisation of tubulin, AKAP4 and centrin 1 confirmed these alterations. Centrin 1 was visible in 67% of spermatozoa (in only 13% centrin localised in a normal position); in the majority of sperm centrin 1's location was altered, sometimes bent; often four spots, indicating the presence of two implantation fossae, were detected. At the centriolar level, immunoreactive fragments, frequently invading the entire short and thick tail, were observed. Centrin 1 is an essential component of the spermatozoa connecting piece and plays a role in centrosome dynamics during sperm morphogenesis and in zygotes and early embryos during spindle assembly. It is important to shed light on these rare conditions in order to better manage the patients during assisted reproductive technology.